Coexistence of superhydrophilicity and superoleophobicity: theory, experiments and applications in oil/water separation. Issue 31 (28th June 2018) - Pan, Yunlu; Huang, Suichu; Li, Feiran; Zhao, Xuezeng; Wang, Weijie
Abstract : A model of the coexistence of superhydrophilicity and superoleophobicity with elaborate experimental proofs. Abstract : The coexistence of superhydrophilicity and superoleophobicity was considered abnormal since a superoleophobic surface would also be superhydrophobic based on the classic surface free energy (SFE) theory. However, several studies have succeeded in preparing uperhydrophilic/superoleophobic surfaces, although the theoretical explanations were still not convincing due to the lack of experimental evidence. In this study, a theory for the coexistence of superhydrophilicity and superoleophobicity was developed with a series of experimental proofs. Four different superhydrophilic/superoleophobic surfaces were prepared as examples and it can be inferred that much more different surfaces with such wettability can be prepared for different specific applications based on the developed theory, and oil/water separations were conducted by using one kind of these prepared surfaces.